Cross-metathesis reaction of α- and β-vinyl C-glycosides with alkenes - Šnajdr, Ivan; Parkan, Kamil; Hessler, Filip; Kotora, Martin (Beilstein Journal of Organic Chemistry, 2015)
Cross-metathesis of α- and β-vinyl C-deoxyribosides and α-vinyl C-galactoside with various terminal alkenes under different conditions was studied. The cross-metathesis of the former proceeded with good yields of the corresponding products in ClCH2CH2Cl the latter required the presence of CuI in CH2Cl2 to achieve good yields of the products. A simple method for the preparation of α- and β-vinyl C-deoxyribosides was also developed. In addition, feasibility of deprotection and further transformations were briefly explored.
Keywords: C-glycosides; catalysis; carbohydrates; cross-metathesis; ruthenium